The #7DaysWithEstrella Campaign on Instagram to Boost Sales of the Unisex Fashion Brand Estrella - Muhammad Zaky Akbar; Intan Zhahira; Mikhael Yulius Cobis (Yayasan Ilomata, 2026)
Estrella uses a unisex concept, meaning that one product design can be worn by both men and women. Estrella utilizes the Instagram platform to conduct the #7DaysWithEstrella campaign, which aims to increase visibility and introduce its unisex products. The campaign was conducted over a consistently defined period of seven days, aligning with the release of seven product units featured throughout the campaign. This study applies a Holistic Marketing approach through Integrated Marketing, which includes four main aspects: communication, products & services, distribution, and pricing. These aspects are implemented throughout the campaign, from planning to evaluation. The campaign’s progress is described using Key Performance Indicators (KPIs), namely changes in follower numbers, the introduction of seven new products, pre-order activity for 15 Estrella items, increases in Instagram viewership, and customer feedback obtained during the campaign period. Rather than claiming campaign effectiveness, these KPIs are presented descriptively to illustrate the observable outcomes within the defined timeframe, without asserting causal success. For future development, sales expansion may be explored through various platforms such as websites and e-commerce marketplaces.